2020
DOI: 10.3390/cancers12030663
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Functions of OCT-3/4 Regulated by Ubiquitination in Proliferating Cells

Abstract: Octamer-binding transcription factor 3/4 (OCT-3/4), which is involved in the tumorigenesis of somatic cancers, has diverse functions during cancer development. Overexpression of OCT-3/4 has been detected in various human somatic tumors, indicating that OCT-3/4 activation may contribute to the development and progression of cancers. Stem cells can undergo self-renewal, pluripotency, and reprogramming with the help of at least four transcription factors, OCT-3/4, SRY box-containing gene 2 (SOX2), Krüppel-like fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 88 publications
(175 reference statements)
0
12
0
Order By: Relevance
“…OCT-3/4 and NANOG regulate the self-renewal, proliferation, survival, and multi-lineage differentiation potential of ESCs. Moreover, these markers not only sustain pluripotency of undifferentiated ESCs but may also act as oncogenes since their overexpression has been identified in several cancers [ 45 , 46 ].…”
Section: Chondrosarcoma Stem Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…OCT-3/4 and NANOG regulate the self-renewal, proliferation, survival, and multi-lineage differentiation potential of ESCs. Moreover, these markers not only sustain pluripotency of undifferentiated ESCs but may also act as oncogenes since their overexpression has been identified in several cancers [ 45 , 46 ].…”
Section: Chondrosarcoma Stem Cellmentioning
confidence: 99%
“…OCT-3/4 and NANOG regulate the self-renewal, proliferation, survival, and multi-lineage differentiation potential of ESCs. Moreover, these markers not only sustain pluripotency of undifferentiated ESCs but may also act as oncogenes since their overexpression has been identified in several cancers [45,46]. Deregulation of sex-determining region Y-Box (SOX) family genes encoding proteins that contribute to cell development, homeostasis, and regeneration [47] was also determined in sarcomas, including ChS.…”
Section: Chondrosarcoma Stem Cellmentioning
confidence: 99%
“…It has been documented that Oct3/4 codes a transcription factor containing the POU homeodomain. C-MYC codes for a nuclear phosphoprotein that controls the progression of the cell cycle [ 17 ]. Evidence has been reported that Oct3/4 and Sox2 are key transcriptional factors that inhibit the expression of genes associated with embryonal stem cell differentiation [ 18 ].…”
Section: Molecular Mechanisms Of Somatic Cells Reprogramming Into Ipscsmentioning
confidence: 99%
“…It has been demonstrated that ubiquitination promotes protein degradation and in the case of Oct3/4 leads to regulation of cellular proliferation and differentiation. Taking it into account, it may be concluded that this factor is not only responsible for cell proliferation but also for the control of their differentiation [ 17 ].…”
Section: Molecular Mechanisms Of Somatic Cells Reprogramming Into Ipscsmentioning
confidence: 99%
“…The abnormal expression of long non-coding RNA (lncRNA) and microRNA (miRNA) can be detected in almost all CRC tumor tissues 5 , 6 LncRNA and miRNA are closely related to the occurrence and development of tumor, and play a very important role of oncogene or tumor suppressor gene in the development of tumor by regulating tumor cell proliferation, invasion, apoptosis and drug resistance 7 , 8 A variety of lncRNAs are closely related to the occurrence and development of CRC; however, their function and mechanisms remain to be fully elucidated. SRY-box containing gene 2 (Sox2) is a key regulatory factor involving vertebrate cell stemness 9 . Sox2 overlapping transcript (SOX2OT) is a lncRNA located overlaps with the SOX2 gene in sequence 10 .…”
Section: Introductionmentioning
confidence: 99%